Kesiapan UMKM Kabupaten Bulungan Dalam Menghadapi Digitaliasasi - Arista, Apriliana Nona; Soimah, Nurus; A, Aslan; Y, Yuliansyah (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The development of MSMEs in entering industry cannot be separated from technology. Technology is used not only in marketing but also in other processes such as production and finance. For this reason, business actors need to prepare themselves to adopt technology. No matter how great and good the technology is, if the human resources who will use it are not ready, it will not be successful. So, the aim of this research is to find out the readiness of MSMEs to face digitalization in Bulungan Regency. This research uses the Technology Readiness Index (TRI) to measure the readiness of MSMEs to adopt technology with four approaches, namely optimism, innovation, discomfort and security. This research uses a quantitative and qualitative approach using questionnaires and questionnaires. The results of this research show that Bulungan Regency MSMEs are in the medium stage as measured by the Technology Readiness Index. MSME owners are optimistic and willing to innovate that technology and digital can change their business in a better direction and do not mind try new things. However, they still feel overwhelmed in the learning process and feel less safe when making digital transactions.